A Single Unexpected Change in Target- but Not Distractor Motion Impairs Multiple Object Tracking. (1st January 2013) - Meyerhoff, Hauke S.; Papenmeier, Frank; Jahn, Georg; Huff, Markus
Recent research addresses the question whether motion information of multiple objects contributes to maintaining a selection of objects across a period of motion. Here, we investigate whether target and/or distractor motion information is used during attentive tracking. We asked participants to track four objects and changed either the motion direction of targets, the motion direction of distractors, neither, or both during a brief flash in the middle of a tracking interval. We observed that a single direction change of targets is sufficient to impair tracking performance. In contrast, changing the motion direction of distractors had no effect on performance. This indicates that target- but not distractor motion information is evaluated during tracking.